Epidemiology and emm types among group A streptococcal pharyngitis in Finland: a prospective laboratory-based study - Virolainen Mirva; Gröndahl‑Yli‑Hannuksela Kirsi; Rantakokko‑Jalava Kaisu; Seiskari Tapio; Lönnqvist Emilia; Kolari Terhi; Rissanen Tiia; Hyyryläinen Hanne-Leena; DICAR study group; Vuopio Jaana (Germany, 2025)
Purpose: Streptococcus pyogenes (mostly termed group A Streptococcus - GAS) is the most important bacterial causative of pharyngitis. However, epidemiology of GAS pharyngitis is not widely established. This study describes GAS pharyngitis cases and emm-type distribution in a prospective study covering over 2 years in two Hospital Districts in Finland.
Methods: A prospective, systematic collection of GAS pharyngitis isolates was conducted between March 2018 and December 2020 in two large Hospital Districts in Finland. Patient characteristics (age, gender) were included if available. All GAS isolates collected were emm typed.
Results: Altogether 1320 GAS pharyngitis strains were collected, 904 in the Hospital District 1 (HD1) and 416 in Hospital District 2 (HD2). In HD1, age and gender data were available. Females were overrepresented (58% of all cases). In addition, the age and gender distributions were noted to be significantly different (p < 0.0001) with females having a more uniform distribution until age of 40. emm28 was common among the age group of 20-29-year-olds and emm89 in children under 10 years of age, respectively. In HD1, most of the isolates were collected during winter and autumn months. Significant differences by season in the frequency of emm12, emm89, emm75 and group of "others" were observed.
Conclusion: Age distribution among GAS pharyngitis cases was significantly different between genders (p < 0.0001). In addition, age group specific and seasonal variations in emm GAS types causing the disease were observed. These findings warrant further investigation, especially for understanding population-based spread of GAS even in more detail.